World records in running: The experience of ergometric analysis - Panova, E. O.; Lazareva, E. A.; Kuptsov, I. M.; Valkina, N. V.; Vavilov, V. V. (Journal of Human Sport & Exercise, 2021)
Analysis of record achievements in athletics has almost a century of history. The leading method during the study was the ergometric measurement method. Ergometric analysis of the results was performed proceeding from the relationship between the length of the distance and the limit time to overcome it. Analysis of record curves at different running distances was performed on the basis of the technique proposed by N.I. Volkov. To analyse the growth of record achievements, we also applied the logarithmic transformation of exponential dependence. Ergometric analysis of record curves displayed that with each new exponential spike in the improvement of results, an increase in the endurance coefficient is noted. It was established that athletes who train to overcome long running distances have better ergometric indicators characterizing aerobic performance: they are characterized by a higher coefficient of "critical speed" and a less pronounced decrease in the curve of the dependence "speed - time". And middle-distance athletes were characterized by large values of power factor, which gives clear advantages upon performing intense muscular work. The data obtained by us in the analysis of record achievements in short distances and the forecast of records for these distances allowed to distinguish four stages throughout the history of record achievements in athletics, within each of which occurred a radical reorganization of the training methodology used.